Unstable Work Schedules and Racial Earnings Disparities Among U.S. Workers - Julie Y. Cai; Marybeth J. Mattingly (RSF: The Russell Sage Foundation Journal of the Social Sciences)
Research demonstrates large and persistence disparities in earnings by race-ethnicity, with white and Asian families generally faring far better than black and Hispanic families. One emerging but underexplored factor that may contribute to racial earnings disparities is unstable work hours. Wage workers often face earnings consequences when volatility is frequent, involuntary, or unanticipated. Leveraging the panel design of the monthly Current Population Survey, we follow a group of hourly workers across a four-month period to assess whether volatility (both magnitude and direction) in the first three months observed relates to their subsequent earnings in the fourth month of observation. We consider how this unfolds when they remain in the same job and when they switch jobs. Substantial volatility, either when work hours increase or decrease, is associated with lower earnings in the near future, both within- and between-jobs. However, when facing more volatile work schedules and substantial changes in month-to-month hours, black workers earn less than white workers when they remain in the same job. This difference is not observed among job changers.